2013
DOI: 10.1096/fj.13-231381
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐1 receptor deficiency in thyrocytes impairs thyroid hormone secretion and completely inhibits TSH‐stimulated goiter

Abstract: Although thyroid-stimulating hormone (TSH) is known to be a major regulator of thyroid hormone biosynthesis and thyroid growth, insulin-like growth factor 1 (IGF-1) is required for mediating thyrocyte growth in concert with TSH in vitro. We generated mice with thyrocyte-selective ablation of IGF-1 receptor (TIGF1RKO) to explore the role of IGF-1 receptor signaling on thyroid function and growth. In 5-wk-old TIGF1RKO mice, serum thyroxine (T4) concentrations were decreased by 30% in concert with a 43% down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 44 publications
(55 reference statements)
5
42
0
1
Order By: Relevance
“…Thus, although GH supplementation cannot restore normal TV in the absence of TSH, it can induce proliferation of thyrocytes and the appearance of thyroid nodules, due to its well-known proliferative and mitogenic effects, regardless of TSH levels. This novel finding fits with recent in vitro studies that proved that goiter development under experimental conditions was completely abrogated in IGF1 receptor knock-out mice, revealing an essential, autonomous role for IGF1 receptor signaling in the regulation of goitrogenesis (31).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, although GH supplementation cannot restore normal TV in the absence of TSH, it can induce proliferation of thyrocytes and the appearance of thyroid nodules, due to its well-known proliferative and mitogenic effects, regardless of TSH levels. This novel finding fits with recent in vitro studies that proved that goiter development under experimental conditions was completely abrogated in IGF1 receptor knock-out mice, revealing an essential, autonomous role for IGF1 receptor signaling in the regulation of goitrogenesis (31).…”
Section: Discussionsupporting
confidence: 89%
“…The authors also observed that short-term treatment using IGF1 induces AKT activation, which may induce the TSHstimulated IGF1R/mTOR/S6 signaling pathways in cultured thyrocytes (Ock et al 2013).…”
Section: Endocrine-related Cancermentioning
confidence: 88%
“…Phenotypes of multiple Igf1r tissue-specific mutant lines were postnatally analyzed after mating them with diverse cell-type Cre-expressing transgenics. Conditional deletion of Igf1r in adult animals was described in many cells including pancreatic beta-cells, osteoblasts, endothelial cells, hepatocytes, prostate epithelium, thyrocytes, adipocytes, oligodendrocytes and neurons, resulting in different cell-or tissue-specific effects, which support IGF1R pleiotropic function (Abbas et al 2011;Boucher et al 2012;Cadoret et al 2005;DiGirolamo et al 2007;Kappeler et al 2008;Kloting et al 2008;Kondo et al 2003;Kulkarni et al 2002;Mason et al 2003;Muller et al 2011;Ock et al 2013;Sutherland et al 2008;Xuan et al 2010;Zeger et al 2007). Absence of IGF1R caused opposite results on different tissues depending on the cell-type specificity of Cre mouse lines.…”
Section: Introductionmentioning
confidence: 99%